2011
DOI: 10.1097/inf.0b013e31820e6e02
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a Single Dose of Tetravalent Meningococcal Serogroups A, C, W-135, and Y Conjugate Vaccine Administered to 2- to 10-year-olds Is Noninferior to a Licensed-ACWY Polysaccharide Vaccine With an Acceptable Safety Profile

Abstract: ACWY-TT was immunogenic in children between 2 to 10 years of age with a clinically acceptable safety profile that resembled licensed Men-PS. These data support a positive benefit/risk ratio for the ACWY-TT vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 27 publications
7
57
0
1
Order By: Relevance
“…Pain at the injection site tended to be reported more frequently for participants who received the MenACWY-TT vaccine than the Men-PS vaccine. This observation is consistent with previous studies showing that injection site reactions are more frequent in individuals vaccinated with MenACWY-TT versus Men-PS (35,36,45,46) and those vaccinated with other quadrivalent meningococcal conjugate vaccines versus plain PS vaccines (47,48). It is likely that the increased reactogenicity following vaccination with the MenACWY-TT vaccine is due to the TT component (49).…”
Section: Discussionsupporting
confidence: 92%
“…Pain at the injection site tended to be reported more frequently for participants who received the MenACWY-TT vaccine than the Men-PS vaccine. This observation is consistent with previous studies showing that injection site reactions are more frequent in individuals vaccinated with MenACWY-TT versus Men-PS (35,36,45,46) and those vaccinated with other quadrivalent meningococcal conjugate vaccines versus plain PS vaccines (47,48). It is likely that the increased reactogenicity following vaccination with the MenACWY-TT vaccine is due to the TT component (49).…”
Section: Discussionsupporting
confidence: 92%
“…MenACWY-TT aşısının çocuk, adolesan, erişkin ve 55-103 yaş arası popülasyonda da immünojenik ve güvenilir olduğu yapılan çalışmalarda gösterilmiştir (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . Baxter ve ark.…”
Section: Menacwy-tt Ile Ilgili Yürütülen Antikor Sürekliliğiunclassified
“…43 In the phase III randomized study by Memish et al, including children 2 to 10 years old from the Philippines, India, Lebanon, and Saudi Arabia, MenACWY-TT vaccine was found to have an acceptable safety profile that was similar to licensed PS vaccine in all vaccinated cohorts. 47 Grade 3 AEs were infrequently reported in both treatment groups and no SAEs occurred that were considered related to vaccination. Local and general solicited AEs in the 2-5 years strata were statistically similar in both groups.…”
Section: Safety Profilementioning
confidence: 99%
“…Vaccine response was statistically significantly higher with MenACWY-TT compared to the PS vaccine. 47 In another study, Dbaibo et al demonstrated the immunogenicity of MenACWY-TT in 271 individuals aged 4.5-34 years either na€ ıve or vaccinated 2.5-3 years earlier with a tetravalent PS vaccine. Those who had been previously vaccinated with a PS vaccine showed lower rSBA titers although more than 97% of all subjects achieved protective rSBA titers 1:128 at one month post vaccination.…”
Section: Immunogenicity Of Menacwy-ttmentioning
confidence: 99%
See 1 more Smart Citation